2007
DOI: 10.1016/j.ygyno.2006.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF) pathway as a therapeutic target in gynecologic malignancies

Abstract: Vascular endothelial growth factor (VEGF) plays a critical role in angiogenesis, which is required for tumor growth and metastasis. In this article, a review of the functional and biological roles of the VEGF pathway in driving angiogenesis and growth of gynecologic malignancies was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 76 publications
0
40
0
Order By: Relevance
“…Targeting the VEGF pathway has provided promising proof that antiangiogenic therapies can indeed improve therapeutic outcomes among cancer patients (37). Initial clinical trials with bevacizumab in ovarian cancer have shown encouraging results (38,39). However, it is likely that additional targets may be required to achieve further gains in patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the VEGF pathway has provided promising proof that antiangiogenic therapies can indeed improve therapeutic outcomes among cancer patients (37). Initial clinical trials with bevacizumab in ovarian cancer have shown encouraging results (38,39). However, it is likely that additional targets may be required to achieve further gains in patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…When the balance is broken in favour of positive regulators, the switch of the angiogenesis malignant tumour phenotype is activated within a complex scenario, in which tumour cells, local blood vessels, angiogenesis-stimulating and -inhibiting factors and various components of the extracellular matrix play a role. This angiogenesis switch is triggered by microenvironmental conditions activating the process, mainly tissular hypoxia and cytokine release [3].…”
Section: Angiogenesis and Ovarian Cancermentioning
confidence: 99%
“…One study analyzed WA's potential for molecular docking through programs such as SwissDock and Docking Server [70]. Current anti-angiogenic therapies approved by the FDA, such as Bevacizumab, have serious to life-threatening side effects, and have little effect on brain tumor invasiveness [71][72][73]. After treatment with Bevacizumab, glioblastomas will adapt by upregulating glycolysis production, moving towards a more anaerobic metabolism, and inducing a microenvironmental acidosis.…”
Section: Effects On Angiogenesismentioning
confidence: 99%